How Can Seventh Graders' Self-Confidence to Speak English Be Fostered Through the Use of ICT's at an EFL Public Institution? (2019)
ABSTRACT: This action research was aimed at fostering the student’s self-confidence to speak English through the use of Information and Communication Technologies (ICT’s) at a public institution in Bello. Data were collected through three oral assignments, a questionnaire to the CT and the students, and a journal. Data analysis demonstrated the potential usefulness of cell phones, videos, PowerPoint presentations, and the video beam to foster students’ self-confidence to speak English because of the interactions they have with the devices. Moreover, a positive impact of these technologies for learning English in general was also found. However, some limitations such as the lack of resources and lack of teaching experience affected the development of the study and kept it from obtaining better results.